Analisis Kesalahan Siswa SD Dalam Menyelesaikan Permasalahan Luas Gabungan Bangun Datar Berdasarkan Watson’s Error Category - Mohammad Nurwahid (Journal on Education, 2021)
Geometry is a branch of mathematics and is one of the subject matter in mathematics in elementary schools. Measurement of area is one of the fundamental topics in mathematics. In fact, with regard to broad measurement skills, most of the students have difficulty in describing the problem. the mistakes that students make in answering a problem or problem need to be identified, the information obtained about errors in answering math problems can be used in improving mathematics teaching and learning activities. The purpose of this study was to identify errors made in solving the broad problem of combining data shapes based on the Watson error category. This type of research is descriptive qualitative research. The subjects used were 6 4th grade students of MI Nurul Huda with three different ability criteria. The selection is based on the advice of the math teacher and the daily test scores of the previous material. The results of the study show that the errors made by the research are missing conclusion errors, incorrect data errors, incorrect procedures, missing data error, and skill hierarchy problem